ASSESSMENT OF PHARMACIST MEDIATED EDUCATION ON KNOWLEDGE, ATTITUDE AND PRACTICES IN TYPE 2 DIABETES MELLITUS PATIENTS IN SOUTH INDIAN RURAL POPULATION - Adepu, Sai Pawan Ramesh; Sam, Steny; Omanakuttan, Cuckoo; K V, Ramanatha; Yegurla, Yashaswini (Innovare Journal Health Sciences, 2018)
Objective: To assess the influence of pharmacist mediated education on knowledge, attitude and practice (KAP) in rural patients with type 2 diabetes mellitus. Â Methodology: This is a prospective, randomized interventional study approved by the institutional ethics committee. Eligible type 2 diabetic patients with written informed consent were enrolled and randomized into control and test group. Validated and local language translated KAP questionnaire was administered to all patients at baseline and three subsequent follow-ups. Patients in the test group received structured education at every follow up whereas the control group patients received education only at the final follow up. SPSS software was used to evaluate the data. Results: Among the 72 patients enrolled, 35 were randomized into control group and 37 into test group. Majority of the study patients (65.2%) were males with an age range of 30 to 72 years and were from agricultural profession (34.72%) with school education (59.7%). The mean Body mass index (BMI) of the study patients was 25.01. At baseline, the mean glycosylated hemoglobin (HbA1C) value of patients was 6.48Â±1.39% in the control group and 6.23Â±1.16% in the test group. During the last follow-up, a significant (p<0.05) improvement was observed in KAP scores in test group patients compared to control group patients which were supported by statistically significant (p<0.05) improvement in Capillary blood glucose (CBG) values. Conclusion: Pharmacist mediated structured education has shown a positive impact on Knowledge Attitude and Practices of test group patients towards their disease management. Keywords: Diabetes, Therapeutic Outcome, Knowledge Attitude & Practice.